The Relation between Self-Regulated Learning and Mathematical Problem-Solving During Covid-19 - Alyani, Fitri; Ramadhina, Anisa Laela (LPPM Undiksha, 2022)
Changes in the learning process that often occur during the Covid-19 period indicate that students need to develop the ability to organize, direct, adjust and control themselves. Self-regulated learning is one of the aspects required in learning during the Covid-19 because Self-Regulated Learning influences mathematical problem-solving abilities. This study is a correlation study which aims to analyze the relation between Self-Regulated Learning and math problem-solving during Covid-19. The sample for this study was drawn from 350 students in grade XI from four public high schools, who were obtained by simple random sampling. Data were collected through Self-Regulated Learning questionnaires and problem-solving ability tests. The data were analyzed using Winsteps and SPSS. Pearson correlation and coefficient of determination tests were conducted to see the relation between the two variables. According to the research conducted, the Pearson correlation coefficient was 0.634, indicating a relation between Self-Regulated Learning and students' math problem-solving during Covid-19. Through the results, it can be seen that the level of students' mathematical problem-solving increases along with the increase in their Self-Regulated Learning. So, this research can encourage students to improve SRL to help them in solving math problems.